3(-16)-y=-9

Simple and best practice solution for 3(-16)-y=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-16)-y=-9 equation:


Simplifying
3(-16) + -1y = -9

Multiply 3 * -16
-48 + -1y = -9

Solving
-48 + -1y = -9

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + -1y = -9 + 48

Combine like terms: -48 + 48 = 0
0 + -1y = -9 + 48
-1y = -9 + 48

Combine like terms: -9 + 48 = 39
-1y = 39

Divide each side by '-1'.
y = -39

Simplifying
y = -39

See similar equations:

| 0.74h=0.74 | | t=7s | | (37.5+10x)-(19.5x)=0.5(x-5)(x-15) | | 0/0=87 | | (6400x/355)*30=9.47 | | 4x=x+6-30 | | u=3(2n+32)+8(n+1) | | y=1E+0.06x+0.8006 | | 7x-3(4x+5)=40 | | 6(2x-3)-2(6-3x)=7(2x-1) | | 7554855845495538412963949835/0 | | 29=w-11 | | 955=5x | | u=3(7n+33)+5(n+1) | | (x+6)-30=4x | | (8-67x)=x | | (k/0.2)-3=7 | | a+0.43=5.2 | | x=30x | | 4y+64=0 | | 7x+7(-3x+11)=-77 | | 57-x/35=-100 | | -5=20x/4 | | -10.5x+37.5=0 | | u=4(7n+31)+7(n+1) | | 5x+9y=45fory | | 7+6745745475475=x | | E=Q-t/t | | -12x+4=4-12x | | 50x=5 | | 60x^2+180=0 | | 6x-4(-2x+12)=64 |

Equations solver categories